If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = -3x + -32 Reorder the terms: 5x = -32 + -3x Solving 5x = -32 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 5x + 3x = -32 + -3x + 3x Combine like terms: 5x + 3x = 8x 8x = -32 + -3x + 3x Combine like terms: -3x + 3x = 0 8x = -32 + 0 8x = -32 Divide each side by '8'. x = -4 Simplifying x = -4
| -3(r-6)=-9 | | 8x+4y=188 | | 6(x-9)-4(x+8)=1 | | 5log(x-5)=12 | | -4m+6=-8 | | -13n-(-2n)-(-15n)+-17n-(-10n)-10=5 | | 2y+4=y+7 | | 3x+3(1-x)=-17 | | 3x-2=5x-2 | | 84=6(m+7) | | (2x-1)+3(3x-5)=-2(2x+1) | | 10y+7=17 | | -x=-2x-1 | | 4q-3q+2q-1=11 | | 6x=2x+105 | | 0.5p+4.1=5.7-0.3p | | F=-2575+35x | | 4x-3=-5x-21 | | 30=2t-17t | | j+2=14 | | 15c=5 | | 2x+105=6x | | N+2n=57 | | -X+3(3)=12 | | -5x+10=-14-x | | 356b+56=-832 | | -17s+13s-8=-12 | | 2y-2y+y=17 | | 3x+1.5=6 | | 54=m(m-3) | | 8j(4k)= | | 15(x)=6+14(x) |